Spontaneous regression of focal nodular hyperplasia: a pathological report. (29th September 2010) - Laumonier, H; Leblanc, F; Balabaud, C; Bioulac-Sage, P
Abstract : Focal nodular hyperplasia (FNH) is a benign tumour of the liver, occurring in 0.6–3% of the general population. Most lesions are diagnosed incidentally. With the increasing use and improvement of diagnostic imaging, FNH is being observed more often. It has been shown, using radiological approaches, that most FNH remain stable, or even regress, over a long follow-up period. In addition, it is extremely rare that FNH were discovered in elderly. However, to our knowledge, there is no pathological report illustrating the regression of FNH. We report here a case showing the pathological changes occurring during the regression phase of FNH, with dense fibrous tissue mixed with arteries replacing hepatocytes nodules.